ANALISIS KINERJA KESEHATAN LPD DAN PENGARUHNYA TERHADAP PERTUMBUHAN ASET LPD KABUPATEN BADUNG - Made Rusmala Dewi S; I Ketut Suwarta; I.G.N. Jaya Agung Widagda K (Faculty of Economics and Business Udayana University, 2014)
The aims of this research are to evaluate the health of LPDs in Badung Regency and to analyse the effect of LPDs in Badung Regency as measured by CAEL analysis, i.e. Capital (Capital Adequacy Ratio), Asset Quality (productive Asset Quality), Earnings (Rentability), and Liquidity on Asset Growth both simultaneously and partially. The sample of this research contains 79 LPDs, which were drawn under the purposive sampling method. The results of the analysis indicate that CAR, KAP, PPAP, ROA, BOPO, LACLR, and LDR simultaneously effect on Asset Growth with coefficient of determination (R2) of 0.37. Partially, only the CAR and KAP ratios have statistically significant effect on Asset Growth. On average, all of the LPDs in the Badung Regency were in healthy condition.